Platform Halal Lifestyle dengan Aplikasi Konsep One Stop Solution - Ativa Hesti Agustina; Risky Dwi Afriadi; Ceasar Pratama; Ade Lestari (Falah: Jurnal Ekonomi Syariah, 2019)
This research focuses on halal lifestyle as a market segment of Indonesian society. In Indonesia which has the largest majority of Muslim population, so the need for halal lifestyle needs for millennials, is faced with the situation of potential halal lifestyle developments that has not been optimally well and demanded by the presence of increasingly advanced technology. This study analyzes the SWOT approach to get answers about the importance of halal lifestyle in Indonesian society. The results of the study introduce and create opportunities and a large market share for Indonesia by using communication technology, especially the internet, which can provide a one stop solution in the form of halal lifestyle applications so as to maintain maqashid syariah.